(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2016)
The law concerning transsexuality was approved in Italy in 1982. The text is ambiguous, as it does not explicitly require any surgical intervention nor sterility of the person, but it mentions «modification of sexual characteristics». For a long time this statement was interpreted by judges in a very strict way, as if implying for a trans-sexual person to have undergone a major operation and be sterile in order to gain legal gender reassignment. In the last two years this jurisprudential trend was challenged by some courts, with decisions in favor of transgender people claiming their right to be recognized under the law without harming their physical integrity. In July 2015 the Court of Cassation (Italy’s court of last resort) endorsed this judicial approach. Finally, on the 21st of October the Constitutional Court decided the issue raised by the Court of Trento, rejecting the doubt that the provision as worded was unconstitutional because it can and must be interpreted in conformity with the Constitution. In its judgment the Court stated that surgical intervention cannot be considered to be a compulsory requisite for obtaining legal gender recognition. Furthermore, the Court acknowledged that each person has the right to choose how to achieve one’s state of personal well-being and frame one’s transition. This comment will discuss the main points of the decision and briefly speculate on its effects and future perspectives.